Bringing Back the Social into the Sociology of Religion: Critical Approaches - Altglas, Véronique (Studies in Critical Research on Religion Ser, 2018)
Intro -- Bringing Back the Social into the Sociology of Religion: Critical Approaches -- Copyright -- Dedication -- Contents -- Series Editor Preface -- List of Illustrations -- Notes on Contributors -- Introduction: An Epistemology for the Sociology of Religion -- 1 Protestant Churches and Same-Sex Marriage in France: "Theological" Criteria and Sociological Approaches -- 2 Deconstructing Archer's (Un)Critical Realism -- 3 Spirituality and Discipline: Not a Contradiction in Terms -- 4 Congregational Studies, Worship and Region Behaviour -- 5 Unmasking the Relations of Power within the Religious Field -- 6 An Affective (U-)Turn in the Sociology of Religion? Religious Emotions and Native Narratives -- 7 "Reverse Mission": A Critical Approach for a Problematic Subject -- 8 "We are Peace-Loving People." Sufism, Orientalist Constructions of Islam and Radicalization -- Index